Sustainable Healthy Diets through Food Systems Transformation – SHiFT launch event in Vietnam report - Huynh Thi Thanh Tuyen; Pham Thi, Huong Mai; Duong, Thanh Thi; Brouwer, Inge D.; Herens, Marion C.; Nguyen, Phuong Hong (2022)
The SHiFT launch event, Vietnam was co-organized by IFPRI, WUR, the Vietnam Academy of Agricultural Sciences (VAAS), the National Institute of Nutrition (NIN), and The Alliance on June 24, 2022, in Hanoi, Vietnam. The main purpose of the workshop was to: (i) Introduce the CGIAR Initiative “Sustainable Healthy Diets through Food Systems Transformation” (SHiFT) in Vietnam; (ii) Explore opinions from partners to identify how SHiFT aligns with the Development Strategy of Vietnam; and (iii) Explore collaborative mechanisms among potential and strategic partners in SHiFT implementation, and for reporting and learning in the SHiFT Initiative to be in line with the food systems transformation process in Vietnam.